Developing a system of testing the knowledge of higher education students within the module «Prospects for the development of decentralized energy in Ukraine and the world» of the discipline «Distributed Generation Systems - Oliinyk, Y.; Cherniuk, A.; Brovko , K. (Problems of Engineer-Pedagogical Education, 2023)
The training of highly qualified specialists and power engineers is now an important and urgent task of the country’s energy sector development. Higher education students, majoring in the specialty 141 «Electric power engineering, electrical engineering and electromechanical engineering» at Ukrainian Engineering Pedagogics Academy, study a number of disciplines necessary for the high-quality modern training of qualified specialists who are bound to be in demand on the labor market upon graduating. One of such disciplines, titled «Distributed Generation Systems», plays the leading role in the process of training qualified engineering personnel in the system of higher education. Achieving a proficient command of educational content necessitates the implementation of effective and punctual knowledge evaluation. Assessment through testing offers several noteworthy benefits, notably an opportunity to impartially gauge the extent of assimilated knowledge and improve retention of instructional materials which is much reinforced when students respond to questions. Hence, the evaluation of the quality of knowledge acquisition within the context of higher education holds a pivotal role in the efficacy of the pedagogical process, affording students and teachers the opportunity to attain a comprehensive grasp of the knowledge acquired, inclusive of aspects that may not have been fully internalized during students’ higher education pursuits. Drawing inspiration from the ideas presented by V.P. Bespalko, models of tests aligned with orientation, conceptual analysis, and analytical synthesis levels of the acquisition of educational materials were formulated. On the basis of these models, the article considers the development of tests of an informative and indicative level to assess the acquisition of an educational element (unit) for identification, distinction and classification of deductive and inductive types. For this, a structural and logical scheme of the discipline «Distributed Generation Systems» was developed with the designation of training elements, the assimilation of which can be verified with the help of the developed orientation tests for identification, differentiation and classification. In the future, the developed tests can be supplemented with tests of productive-analytical and productive-synthetic levels of learning.